In vitro activity of naturally occurring peptides (defensins) against Listeria monocytogenes Ação in vitro de peptídeos naturais (defensinas) sobre Listeria monocytogenes - Maria da Graça F. Nascimento; James S. Cullor; Michael E. Selsted (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 1994)
Autoclaved distilled water samples were inoculated with L. monocytogenes strain V7 and strain VPH-1, and incubated aerobically, at 30 C for 48 hours. Each strain was tested individually, and growth curves were determined at 1, 2, 3, 4, 5, 21, 24, and 48 hours. The growth or survival of L. monocytogenes was similar for both strains, with survivors at 24 hour-incubation. The microbicidal activity of one synthetic cationic peptide (NP-2) was examined against L. monocytogenes strain V7, in a water system. Antibacterial activity of NP-2 (1, 5, and 10 g/ml) was best expressed at 60 minute-incubation, with 10 g/ml of peptide, at 30 C. Amostras de água destilada, autoclavadas, foram inoculadas com L. monocytogenes cepa V7 e cepa VPH-1, e incubadas, aerobicamente, a 30ºC por 48 horas. Cada cepa foi testada individualmente, e determinou-se curvas de crescimento a 1, 2, 3, 4, 5, 21, 24, e 48 horas. O crescimento ou sobrevivência das duas cepas foi semelhante e encontrou-se sobreviventes em 24 horas de incubação. Examinou-se a atividade bactericida de um dos peptídeos catiônicos sintéticos (NP-2) contra L. monocytogenes cepa V7, em sistema aquoso. A atividade antibacteriana de NP-2 (1, 5, and 10µg/ml) foi melhor aos 60 minutos de incubação, com 10µg/ml de peptídeo, a 30 C.